The Role and Future of Endoscopic Spine Surgery: A Narrative Review - Kwon, Hyungjoo; Park, Jeong-Yoon (Neurospine, 2023)
Many types of surgeries are changing from conventional to minimally invasive techniques. Techniques in spine surgery have also changed, with endoscopic spine surgery (ESS) becoming a major surgical technique. Although ESS has advantages such as less soft tissue dissection and normal structure damage, reduced blood loss, less epidural scarring, reduced hospital stay, and earlier functional recovery, it is not possible to replace all spine surgery techniques with ESS. ESS was first used for discectomy in the lumbar spine, but the range of ESS has expanded to cover the entire spine, including the cervical and thoracic spine. With improvements in ESS instruments (optics, endoscope, endoscopic drill and shaver, irrigation pump, and multiportal endoscopic), limitations of ESS have gradually decreased, and it is possible to apply ESS to more spine pathologies. ESS currently incorporates new technologies, such as navigation, augmented and virtual reality, robotics, and 3-dimentional and ultraresolution visualization, to innovate and improve outcomes. In this article, we review the history and current status of ESS, and discuss future goals and possibilities for ESS through comparisons with conventional surgical techniques.